Substrate-dependent modulation of the enzymatic catalytic activity: Reduction of nitrate, chlorate and perchlorate by respiratory nitrate reductase from Marinobacter hydrocarbonoclasticus 617 - Marangon, Jacopo (2012)
The respiratory nitrate reductase complex (NarGHI) from Marinobacter hydrocarbonoclasticus 617 (Mh, formerly Pseudomonas nautica 617) catalyzes the reduction of nitrate to nitrite. This reaction is the first step of the denitrification pathway and is coupled to the quinone pool oxidation and proton translocation to the periplasm, which generates the proton motive force needed for ATP synthesis. The Mh NarGH water-soluble heterodimer has been purified and the kinetic and redox properties have been studied through in-solution enzyme kinetics, protein film voltammetry and spectropotentiometric redox titration. The kinetic parameters of Mh NarGH toward substrates and inhibitors are consistent with those reported for other respiratory nitrate reductases. Protein film voltammetry showed that at least two catalytically distinct forms of the enzyme, which depend on the applied potential, are responsible for substrate reduction. These two forms are affected differentially by the oxidizing substrate, as well as by pH and inhibitors. A new model for the potential dependence of the catalytic efficiency of Nars is proposed.